Physiological and Biochemical Responses of Bicarbonate Supplementation on Biomass and Lipid Content of Green Algae Scenedesmus sp. BHU1 Isolated From Wastewater for Renewable Biofuel Feedstock - Singh, Rahul Prasad; Yadav, Priya; Kumar, Ajay; Hashem, Abeer; Al-Arjani, Al-Bandari Fahad; Abd_Allah, Elsayed Fathi; Rodríguez Dorantes, Angélica; Gupta, Rajan Kumar (Frontiers in Microbiology, 2022)
In the present study, different microalgae were isolated from wastewater environment and evaluated for higher growth and lipid accumulation. The growth adaptability of all the isolated microalgae were tested for carbon source with supplementation of sodium bicarbonate in BG-11N+ medium. Further on the basis of uptake rate of sodium bicarbonate and growth behavior, microalga strains were selected for biofuel feedstock. During the study, growth parameters of all the isolates were screened after supplementation with various carbon sources, in which strain Scenedesmus sp. BHU1 was found highly effective among all. The efficacy of Scenedesmus sp. BHU1 strain under different sodium bicarbonate (4−20 mM) concentration, in which higher growth 1.4 times greater than control was observed at the concentration 12 mM sodium bicarbonate. In addition, total chlorophyll content (Chl-a + Chl-b), chlorophyll fluorescence (Fv/Fm, Y(II), ETR max and NPQmax), biomass productivity were found to be 11.514 µg/ml, 0.673, 0.675, 31.167 µmol electrons m-2s-1, 1.399, 59.167 mg/L/day respectively at the 12 mM sodium bicarbonate. However, under optimum sodium bicarbonate supplementation, 56.920% carbohydrate and 34.693% lipid content were accumulated, which show potential of sodium bicarbonate supplementation in renewable biofuel feedstock by using Scenedesmus sp. BHU1 strain.